Cultural Policy for Arts Education : African-European Practises and Perspectives - Schneider, Wolfgang; Hardie, Yvette; Akuno, Emily Achieng'; Gad, Daniʾel (2022)
Arts Education institutions and programs create an excellent framework for personality development: learning knowledge, learning skills and learning life. Their attainment requires education to be a holistic concept of advancement that includes aesthetic practice and involvement with the arts. It challenges them to use their actions to think about the meaning of life, in as much as everyone can use artistic experiences to affirm and interrogate their self-image. The Research Program of the UNESCO Chair in Cultural Policy for the Arts in Development at the University of Hildesheim in Germany brought together experts from the Universities in Dar Es Salam, Kampala, Nairobi, Pretoria, Johannesburg, Casablanca and Tunis and further independent researchers to exchange concepts in Cultural Policy for Arts Education.